2010
DOI: 10.1007/s10648-010-9144-5
|View full text |Cite
|
Sign up to set email alerts
|

Video Feedback in Education and Training: Putting Learning in the Picture

Abstract: This meta-analysis demonstrates that the video feedback method has a statistically significant effect on the interaction skills of professionals in a range of contact professions. The aggregate effect, calculated on the basis of 217 experimental comparisons from 33 experimental studies involving a total of 1,058 people, was 0.40 standard deviation (SE=0.07). The effects of training were greater for programs working with a standard observation form of target skills that were central to the program. Results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
173
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 97 publications
9
173
0
4
Order By: Relevance
“…Fragment 2), which seems to distract their attention from the instructional agenda: to focus on professionally relevant aspects of teamwork. In line with Fukkink et al (2011), the results of this study show that unguided seeing could lead to a focus on superficial impressions and could require instructional efforts that redirect the participants' attention to substantial aspects. Without further guidance, novices might Bfind themselves at sea, in a stream of continuous detail they don't know how to parse during the course of their real-time viewing in order to make sense of it^ (Erickson 2007, p. 146).…”
Section: Discussionsupporting
confidence: 81%
“…Fragment 2), which seems to distract their attention from the instructional agenda: to focus on professionally relevant aspects of teamwork. In line with Fukkink et al (2011), the results of this study show that unguided seeing could lead to a focus on superficial impressions and could require instructional efforts that redirect the participants' attention to substantial aspects. Without further guidance, novices might Bfind themselves at sea, in a stream of continuous detail they don't know how to parse during the course of their real-time viewing in order to make sense of it^ (Erickson 2007, p. 146).…”
Section: Discussionsupporting
confidence: 81%
“…The trainer provided the teachers with extensive feedback, because learning about teaching is enhanced when the approaches that are advocated in the CPD programme are modelled by the teacher educator who is delivering the CPD programme (Korthagen, Loughran, & Russell, 2006). A considerable part of the CPD programme consisted of video-based learning, since research has shown that the use of videos can yield positive effects on teachers' beliefs and on their interaction skills (Fukkink, Trienekens, & Kramer, 2011;Van Es & Sherin, 2010).…”
Section: Contextmentioning
confidence: 99%
“…This may be particularly important in situations or conversational moments when change recipients are already highly resistant to change. Again, the observational method seems to be especially useful for sensitizing change agents for their own communication behaviour (Fukkink, Trienekens, & Kramer, 2011). Videotaped interactions are a preferable method in communication training (Kurtz, Silverman, & Draper, 2005).…”
Section: Practical Implicationsmentioning
confidence: 99%